IFNgamma response to Mycobacterium tuberculosis, risk of infection and disease in household contacts of tuberculosis patients in Colombia. - Helena del Corral; Sara C París; Nancy D Marín; Diana M Marín; Lucelly López; Hanna M Henao; Teresita Martínez; Liliana Villa; Luis F Barrera; Blanca L Ortiz; María E Ramírez; Carlos J Montes; et al. (PLoS ONE)
Objectives Household contacts (HHCs) of pulmonary tuberculosis patients are at high risk of Mycobacterium tuberculosis infection and early disease development. Identification of individuals at risk of tuberculosis disease is a desirable goal for tuberculosis control. Interferon-gamma release assays (IGRAs) using specific M. tuberculosis antigens provide an alternative to tuberculin skin testing (TST) for infection detection. Additionally, the levels of IFNgamma produced in response to these antigens may have prognostic value. We estimated the prevalence of M. tuberculosis infection by IGRA and TST in HHCs and their source population (SP), and assessed whether IFNgamma levels in HHCs correlate with tuberculosis development. Methods A cohort of 2060 HHCs was followed for 2-3 years after exposure to a tuberculosis case. Besides TST, IFNgamma responses to mycobacterial antigens: CFP, CFP-10, HspX and Ag85A were assessed in 7-days whole blood cultures and compared to 766 individuals from the SP in Medellín, Colombia. Isoniazid prophylaxis was not offered to child contacts because Colombian tuberculosis regulations consider it only in children under 5 years, TST positive without BCG vaccination. Results Using TST 65.9% of HHCs and 42.7% subjects from the SP were positive (OR 2.60, p<0.0001). IFNgamma response to CFP-10, a biomarker of M. tuberculosis infection, tested positive in 66.3% HHCs and 24.3% from the SP (OR = 6.07, p<0.0001). Tuberculosis incidence rate was 7.0/1000 person years. Children <5 years accounted for 21.6% of incident cases. No significant difference was found between positive and negative IFNgamma responders to CFP-10 (HR 1.82 95% CI 0.79-4.20 p = 0.16). However, a significant trend for tuberculosis development amongst high HHC IFNgamma producers was observed (trend Log rank p = 0.007). Discussion CFP-10-induced IFNgamma production is useful to establish tuberculosis infection prevalence amongst HHC and identify those at highest risk of disease. The high tuberculosis incidence amongst children supports administration of chemoprophylaxis to child contacts regardless of BCG vaccination.